The indifference of young people in Colombia to politics (2018)
Through the present essay, we seek to analyze the main causes, why young people in Colombia are apathetic to participate in political life, considering the behavior of today's society, the statistical studies of recent years and the perception of youth before governments, to formulate strategies that allow for more active involvement of young people in the political world and democratic participation.